PENGARUH KERAGAMAN PRODUK, HARGA DAN LOKASI TERHADAP KEPUASAN KONSUMEN PADA DUTA MINIMARKET MIMBAAN SITUBONDO - Ediyanto, Ediyanto (Relawan Jurnal Indonesia, 2022)
This study uses statistical applications. The population in this study were customers who visited Duta Minimarket Mimbaan Situbondo. The sample used was 99 respondents and used a simple random sampling method. Data collection was carried out using a questionnaire. The data analysis technique used in this study is multiple linear regression analysis. The results of the t test show that all the independent variables (product variety, price, location) have a positive effect on the dependent variable, namely repeat purchases. Multiple linear regression analysis shows that Y = -1.005 E-16 + 0.290 X1 + 0.346 X2 + 0.404 X3 + e. The standard error is 0.080, meaning that all variables calculated in the SPSS version 22 test for Windows 10 have a confounding variable level of 0.080. The results of the t test, tcount product diversity (2.042), price (3.594) and location (4.447). The diversity of products, prices and locations have a partial effect on customer satisfaction tcount > ttable. The results of the F test show Fcount > Ftable, namely 19.855 > 2.70. The coefficient of determination (adjusted R2) obtained is 0.385. This means that 38.5% of consumer satisfaction is influenced by product variety, price and location variables. The remaining 61.5% is influenced by other variables.